2009
DOI: 10.1051/0004-6361/200811081
|View full text |Cite
|
Sign up to set email alerts
|

Star complexes and stellar populations in NGC 6822

Abstract: Aims. The star complexes (large scale star forming regions) of NGC 6822 were traced and mapped and their size distribution was compared with the size distribution of star complexes in the Magellanic Clouds (MCs). The spatial distributions of different age stellar populations were compared with each other. Methods. The star complexes of NGC 6822 were determined by using the isopleths, based on star counts, of the young stars of the galaxy, using a statistical cutoff limit in density. In order to map them and de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
7

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 27 publications
1
18
0
7
Order By: Relevance
“…For the same galaxy, Battinelli et al (1996) found hierarchical structures on two levels, the first with size ∼100 pc and the second with a distribution of sizes from ∼100 to ∼800 pc with maximum at ∼200 pc, in the middle of our aggregates range, and an indication of a peak at ∼400 pc (complexes). Similar were the findings for LMC (Livanou et al 2007) and NGC 6822 (Karampelas et al 2009), where star complexes were detected in two ranges, from 150-400 pc, so roughly what we considered as aggregates. The second was 400-800 pc, in the complexes range.…”
Section: Comparison With Previous Investigationssupporting
confidence: 88%
See 2 more Smart Citations
“…For the same galaxy, Battinelli et al (1996) found hierarchical structures on two levels, the first with size ∼100 pc and the second with a distribution of sizes from ∼100 to ∼800 pc with maximum at ∼200 pc, in the middle of our aggregates range, and an indication of a peak at ∼400 pc (complexes). Similar were the findings for LMC (Livanou et al 2007) and NGC 6822 (Karampelas et al 2009), where star complexes were detected in two ranges, from 150-400 pc, so roughly what we considered as aggregates. The second was 400-800 pc, in the complexes range.…”
Section: Comparison With Previous Investigationssupporting
confidence: 88%
“…We compared our results with those derived in a number of studies of other galaxies, M101 and LMC (B98, Kennicut, Stetson 1996, BKS), LMC (Gouliermis et al 2003), M33, M31, SMC (Battinelli et al 1996), NGC 6822 (Karampelas et al 2009;Gouliermis et al 2010), and HST galaxies .…”
Section: Comparison With Previous Investigationsmentioning
confidence: 93%
See 1 more Smart Citation
“…A barlike structure traced by younger stars in Gouliermis et al (2010) cannot be distinguished in the C/M ratio distribution. The area investigated by Karampelas et al (2009) corresponds to the field of Fig. 14. Beyond that, the density of stars is too low and it is difficult to estimate the C/M ratio.…”
Section: C/m Ratio and Metallicity Distributionmentioning
confidence: 99%
“…The star-count methodology is well known and has been used by several researchers (e.g., Lada & Lada 1995;Carpenter et al 1995Carpenter et al , 2000Kumar et al 2004Kumar et al , 2006. The method can be refined by using different bin sizes in order to investigate large-scale structures, as well as smaller scale subclustering (e.g., Kumar et al 2004;Kirsanova et al 2008), and/or also by smoothing the binned data over adjacent bins (e.g., Karampelas et al 2009). …”
Section: Star Cluster Candidate Finding Methodsmentioning
confidence: 99%